Sustaining more Inclusive Growth in the Republic of Congo - Hakura, Dalia (Departmental Papers; Departmental Paper ;, 2015)
The Republic of Congo has seen dramatic improvement in its debt situation since 2010, following debt relief through the IMF and World Bank Heavily Indebted Poor Countries/Multilateral Debt Relief Initiative. Large oil revenues have allowed the country to boost spending and increase foreign exchange reserves. Yet poverty and inequality remain comparatively high. This paper examines Congo's challenge to manage its natural resource revenue and attain sustained inclusive growth.